Pengaruh Fitur, Kemudahaan Penggunaan dan Customer Perceived Value terhadap Loyalitas Nasabah Pengguna BSI Mobile - Monika, Oni; Rifaatul Indana (FEBI UIN Sunan Kalijaga, 2025)
Mobile banking has become one of the most popular banking services in Indonesia, offering convenience and flexibility in conducting financial transactions. However, with the increasing number of mobile banking services, customer loyalty has become a key factor in retaining customers. This study aims to determine the effect of features, ease of use, and customer perceived value on customer loyalty of BSI Mobile users in the Special Region of Yogyakarta with a sample size of 100 respondents. The method used is a quantitative approach with purposive sampling method. The analytical tool used is IBM SPSS Statistics 30 software. The results of this study show that the variables of ease of use and customer perceived value have a significant effect on customer loyalty. While the feature variable does not have a significant effect on customer loyalty of BSI Mobile users in the Special Region of Yogyakarta.